1993
DOI: 10.1159/000100667
|View full text |Cite
|
Sign up to set email alerts
|

A Tissue Equivalent Phantom for Stereotactic Radiosurgery Localization and Dose Verification

Abstract: A tissue equivalent head phantom was utilized in the stereotactic localization and dose verification of radiosurgery procedures with the Leksell Gamma Knife Unit at the University of Kentucky Medical Center. A radiation dose-dependent color-doped gel target was positioned within the head phantom and stereotactically localized using either angiography, CT, or MR techniques. Utilizing standard Gamma Knife treatment procedures, the head phantom was irradiated, which resulted in a color change of the gel tumor at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Instead of two-dimensional imaging on thin films, it is also possible to produce high-resolution three-dimensional radiographic registration on clear gels or block polymers containing leuco dyes, 11 acid-forming halogenated hydrocarbons containing indicator dye, 12 or a gel solution of ferrous sulfate in the presence of benzoic acid and an indicator dye that upon irradiation forms a highly colored ferric-ion complex with the dye. 93 Although a detailed description of this new technology is not included as part of the current report, it is creating considerable excitement in the medical community and is mentioned in this section on future developments to provide the reader with a few key references. Enthusiasm about the use of gels seems to center on the possibility of measuring three-dimensional ͑3D͒ dose distributions without the problem of having to accurately register a series of films in 3D space.…”
Section: Future Directionsmentioning
confidence: 99%
“…Instead of two-dimensional imaging on thin films, it is also possible to produce high-resolution three-dimensional radiographic registration on clear gels or block polymers containing leuco dyes, 11 acid-forming halogenated hydrocarbons containing indicator dye, 12 or a gel solution of ferrous sulfate in the presence of benzoic acid and an indicator dye that upon irradiation forms a highly colored ferric-ion complex with the dye. 93 Although a detailed description of this new technology is not included as part of the current report, it is creating considerable excitement in the medical community and is mentioned in this section on future developments to provide the reader with a few key references. Enthusiasm about the use of gels seems to center on the possibility of measuring three-dimensional ͑3D͒ dose distributions without the problem of having to accurately register a series of films in 3D space.…”
Section: Future Directionsmentioning
confidence: 99%
“…A system that employs a chemical dosimeter (ferrous sulfate solution) fixed in an aqueous gel and evaluated with magnetic resonance imaging (MRI) has been proposed to verify the 3D radiation dose mapping 5 9 . More recently, the BANG polymer gel in combination with an MRI has been shown to record and accurately map 3D dose distributions with high spatial resolution and precision 10 14 .…”
Section: Introductionmentioning
confidence: 99%
“…The Fricke-agarose gel dosimetry has been widely employed in recent years to measure radiation dose distribution. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] It has been shown that the oxidation of ferrous ions to ferric ions by irradiating a Fricke-agarose gel alters the gel's spin-lattice relaxation rate (R1) and the change in R1 is linearly proportional to the absorbed dose. Compared to the conventional Fricke solution, the Fricke-agarose dosimeter gel has the advantages of a higher sensitivity and, owing to its semi-stiffness property, provides a better way to contain the oxidized ferric ions for the subsequent magnetic resonance ͑MR͒ imaging to take place.…”
Section: Introductionmentioning
confidence: 99%